Laccase, an Emerging Tool to Fabricate Green Composites: A Review - Mohammed, Nasir; Rokiah, Hashim; Othman, Sulaiman; Noor Afeefah, Nordin; Junidah, Lamaming; Mohd, Asim (NC State University, 2015)
In the last two decades, laccases have received much attention from researchers because of their specific ability to oxidize lignin. This function of laccase is very useful for applications in several biotechnological processes, including delignification in the pulp and paper industry and the detoxification of industrial effluents from the textile and petrochemical industries. This review focuses on laccase-mediated fiberboard synthesis. Growing concerns regarding the emission of formaldehyde from wood composites has prompted industrialists to consider the fabrication of green composites. Laccase-mediated fiber treatments oxidize the lignin component without affecting the cellulose structure. As a result, free radicals are generated on the fiber surface, and these can act as potential reactive sites for further cross-linking reactions in board manufacturing. Binderless fiberboards prepared using such methods can be considered as green composites because the manufacturing process involves no additional resin.